Self-rated health among migrants from the former Soviet Union in Germany: a cross-sectional study - Stolpe, Susanne; Ouma, Mary; Winkler, Volker; Meisinger, Christa; Becher, Heiko; Deckert, Andreas (BMJ open, 2018)
Objectives: To assess the status and change in self-rated health among Aussiedler, ethnic German immigrants from the former Soviet Union, as a predictor for premature death 10 years after first assessment. Moreover, to identify subgroups which are particular at risk of anticipated severe health impairment. DESIGN: Cross-sectional questionnaire. Setting: The study was conducted in the catchment area of Augsburg, a city in southern Bavaria, Germany, in 2011/2012 that has a large community of Aussiedler. Participants: 595 Aussiedler (231 male, 364 female, mean age 55 years) who in majority migrated to Germany between 1990 and 1999. Outcome: Primary outcome: self-rated health (very good/good/not so good/bad) and its association with demographic, social and morbidity related variables. Methods: Self-rated health was dichotomised as 'very good' and 'good' versus 'not so good' and 'bad'. Multivariable logistic models were created. Missing values with regard to pain were addressed by a second analysis. Results: Although low response suggests a healthier sample, the findings are alarming. Altogether47% of the Aussiedler perceived their health as less than good, which is worse compared with the first assessment in 2000 (25% compared with 20% of the general public). Prevalence of high blood pressure was present in 52% of Aussiedler, 34.5% were obese, 40.7% suffered from frequent pain and 13.1% had diabetes mellitus. According to the multivariable models, individuals suffering from pain, limited mobility, diabetes mellitus and high blood pressure are particularly in jeopardy. Conclusions: 10 years after the first assessment of self-rated health among Aussiedler their situation deteriorated. Tailored risk factor counselling of general practitioners is highly recommended.
Gesehen am 17.04.2020